2016
DOI: 10.1080/13880209.2016.1260598
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses inflammatory cytokines and heat shock protein 70 release and improves metabolic parameters during experimental sepsis

Abstract: Context: Curcumin has been reported to have anti-inflammatory, antioxidant and hypoglycaemic properties, besides reducing mortality in sepsis.Objective: This study evaluates the biological activities of a curcumin dispersion formulated by spray-drying in experimental sepsis.Materials and methods: Male Wistar rats were subjected to sepsis by caecal ligation and puncture (CLP), controls were sham operated. The animals were treated with curcumin dispersion (100 mg/kg, p.o.) or water for 7 days prior to CLP and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 63 publications
(63 reference statements)
0
32
1
1
Order By: Relevance
“…The bacteria used in dairy (i.e., the sour cream on the mashed potatoes) increase IL-1β, TNFα, and IFNγ (218, 219). Cumin, a spice commonly used in Indian cuisine, reduces expression of inflammatory cytokines CXL-1 and−2, TNFα, IL-1β, IL-6, and IL-18 (220, 221). Chocolate increases IL-10 and IL-1β (222).…”
Section: Peripheral Cytokines In Me/cfsmentioning
confidence: 99%
“…The bacteria used in dairy (i.e., the sour cream on the mashed potatoes) increase IL-1β, TNFα, and IFNγ (218, 219). Cumin, a spice commonly used in Indian cuisine, reduces expression of inflammatory cytokines CXL-1 and−2, TNFα, IL-1β, IL-6, and IL-18 (220, 221). Chocolate increases IL-10 and IL-1β (222).…”
Section: Peripheral Cytokines In Me/cfsmentioning
confidence: 99%
“…In other study conducted by Silva et al (), 100 mg/kg/day curcumin in the form of oral gavage were reduced for 7 days by the proinflammatory cytokines and heat shock protein (HSP70) production and temporarily increased their survival rate.…”
Section: Resultsmentioning
confidence: 93%
“…In other study conducted by Silva et al (2017), 100 mg/kg/day curcumin in the form of oral gavage were reduced for 7 days by the proinflammatory cytokines and heat shock protein (HSP70) production and temporarily increased their survival rate. Madan and Ghosh (2003) demonstrated that oral curcumin supplementation for 7 days decreases the expression of ICAM-1 and vascular cell adhesion molecule 1 (VCAM-1) in liver and lungs and suppresses the migration and infiltration of neutrophils from blood vessels to the liver tissue.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Although numerous strategies have been explored for the treatment of sepsis, affected patients still have an increased risk of mortality (6,7). A previous study also demonstrated that a reduction of inflammatory factors significantly improved metabolic parameters that are beneficial for survival in septic rats (8). In addition, distinct shock phenotypes were apparent, and the effect of early resuscitation according to protocols has been examined in selected cohorts of patients with septic shock (9).…”
Section: Introductionmentioning
confidence: 99%